Seven new species of phytoseiid mites (Acari: Mesostigmata) from Tripura, north-eastern India - Kar, Anamika; Karmakar, Krishna (Zootaxa, 2022)
Tripura is a north eastern hilly state of India, and so far only 27 species of Phytoseiidae have been reported from the state. During the present survey 250 specimens were collected belonging to seven new species, namely Euseius tripuraensis sp. nov., Euseius spontaneum sp. nov., Euseius tripurii sp. nov., Phytoseius birbikrami sp. nov., Phytoseius khowaiensis sp. nov., Phytoseius baramuracus sp. nov., and Typhlodromus (Anthoseius) sonajhuriae sp. nov.